IMPLEMENTASI DAN PERANCANGAN KAMERA NIRKABEL MENGGUNAKAN RASPBERRY PI - AYYINA DEWI PARWATI (Teknik: Jurnal Ilmu Teknik dan Informatika, 2022)
The design of a camera becomes smarter by using a raspberry pi device so that it can monitor and control a location or place and provide mitigation reports through the telegram social media application to a smartphone that has been set to the device. So that with the Raspberry Pi device and this camera module, it can be more comfortable, safer and faster to know and control the situation in the places we want. So from the explanation above, the title of this research is the Implementation and Design of the Raspberry Pi Wireless Camera.